A framework and use cases for big data in procurement. (4th November 2020) - Zeisel, Stefan
Big data has become a buzzword that is broadly discussed in media and board rooms alike. However, in the procurement function there are few visible practical applications of a full-fledged big data scenario so far. Some academic research has been conducted as well as several practitioners' surveys, but insights on how procurement can profit from big data applications are very fragmented. Therefore, the following article portrays a conceptual framework for big data applications in the procurement function connecting different data sources, skilled teams, and big data analytics. Furthermore, a full array of existing and new use cases for procurement is derived.